Effect of Different Sports Practice on Sleep Quality and Quality of Life in Children and Adolescents: Randomized Clinical Trial - Rosa, Camila Cassemiro [UNESP]; Tebar, William Rodrigues [UNESP]; Oliveira, Crystian Bittencourt Soares; Farah, Breno Quintella; Casonatto, Juliano; Saraiva, Bruna Thamyres Ciccotti [UNESP]; Christofaro, Diego Giulliano Destro [UNESP] (Springer Nature, 2021)
Background: Sports practice can promote several health benefits in pediatric populations; nonetheless, most of the studies that investigated these benefits are of cross-sectional design. Thus, our objective was to verify the effectiveness of two types of physical activities through sports, judo and ball games (soccer, volleyball, handball, and basketball) on the quality of sleep and life of Brazilian children and adolescents. Methods: The study is a randomized clinical trial, conducted with 65 participants of both sexes (6–15 years old) in a philanthropic institution in Brazil. The variables investigated were the quality of sleep and life, using the mini-sleep questionnaire and KidsCreen-52 questionnaires (this instrument has a scale ranging from 0 to 100, where 100 is the best value for each domain), respectively. The interventions carried out during 12 weeks (twice a week) were judo and ball games. In the statistical analysis, analysis of variance (ANOVA) for repeated measures was used and the level of statistical significance used was 5%. Results: Judo (P = 0.032) and ball games (P = 0.005) contributed to improving the quality of sleep in the participants. Considering the score of the domains of quality of life, judo and ball games significantly increased the perception of health and physical activity [mean = 6.9 (8.3%) and 8.91 (12.2%) points, respectively], autonomy [mean = 5.81 (7.3%) and 5.00 (6.9%) points], friends and social support (mean = 2.83 (3.8%) and 12.00 (15.9%) points), provocation and bullying [mean = 10.21 (18.1%) and 2.14 (4.1%) points]. Conclusion: It is concluded that both judo and ball games brought benefits to the quality of sleep and life of children and adolescents. Health promotion actions should encourage the increase in sports practice in children and adolescents to improve sleep and quality of life.
Keywords: Children and adolescents; Motor behavior; Physical activity; Quality of life; Sleep quality; Sport